mRNA-based therapy in a rabbit model of variegate porphyria offers new insights into the pathogenesis of acute attacks - Daniel Jericó; Karol M. Córdoba; Lei Jiang; Caroline Schmitt; María Morán; Ana Sampedro; Manuel Alegre; María Collantes; Eva Santamaría; Estíbaliz Alegre; Corinne Culerier; Ander Estella-Hermoso de Mendoza; et al. (Elsevier, 2021)
Variegate porphyria (VP) results from haploinsufficiency of protoporphyrinogen oxidase (PPOX), the seventh enzyme in the heme synthesis pathway. There is no VP model that recapitulates the clinical manifestations of acute attacks. Combined administrations of 2-allyl-2-isopropylacetamide and rifampicin in rabbits halved hepatic PPOX activity, resulting in increased accumulation of a potentially neurotoxic heme precursor, lipid peroxidation, inflammation, and hepatocyte cytoplasmic stress. Rabbits also showed hypertension, motor impairment, reduced activity of critical mitochondrial hemoprotein functions, and altered glucose homeostasis. Hemin treatment only resulted in a slight drop in heme precursor accumulation but further increased hepatic heme catabolism, inflammation, and cytoplasmic stress. Hemin replenishment did protect against hypertension, but it failed to restore action potentials in the sciatic nerve or glucose homeostasis. Systemic porphobilinogen deaminase (PBGD) mRNA administration increased hepatic PBGD activity, the third enzyme of the pathway, and rapidly normalized serum and urine porphyrin precursor levels. All features studied were improved, including those related to critical hemoprotein functions. In conclusion, the VP model recapitulates the biochemical characteristics and some clinical manifestations associated with severe acute attacks in humans. Systemic PBGD mRNA provided successful protection against the acute attack, indicating that PBGD, and not PPOX, was the critical enzyme for hepatic heme synthesis in VP rabbits.